2000
DOI: 10.1097/00005082-200004000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Elder and Family Caregiver Satisfaction with Discharge Planning

Abstract: Client satisfaction is considered an important outcome measure in a managed care environment faced with escalating health care costs, shortened lengths of hospital stay, and competition among acute care hospitals. With shortened lengths of stay in acute care hospitals, discharge planning has assumed increased importance, particularly for elders who have chronic conditions, such as heart failure, that require follow-up care. Consequently, understanding the predictors of client satisfaction with discharge planni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 23 publications
1
63
0
5
Order By: Relevance
“…4 Under these circumstances, ineffective planning and coordination of care can undermine patient satisfaction, facilitate adverse events, and contribute to more frequent hospital readmissions. [5][6][7][8] Following hospital discharge nearly half (49%) of hospitalized patients experience at least 1 medical error in medication continuity, diagnostic workup, or test follow-up. 7 It has been reported that 19%-23% of patients suffer an adverse event, most frequently an adverse drug event (ADE).…”
mentioning
confidence: 99%
“…4 Under these circumstances, ineffective planning and coordination of care can undermine patient satisfaction, facilitate adverse events, and contribute to more frequent hospital readmissions. [5][6][7][8] Following hospital discharge nearly half (49%) of hospitalized patients experience at least 1 medical error in medication continuity, diagnostic workup, or test follow-up. 7 It has been reported that 19%-23% of patients suffer an adverse event, most frequently an adverse drug event (ADE).…”
mentioning
confidence: 99%
“…This reaction results from the comparison between the care received and a subjective criterion, i.e. the clients' perception or expectation (16) .…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the physical, psychosocial and economic concerns of patients, as well as their goals and wishes, is essential to facilitate the behavioural changes necessary for self-care. Other important characteristics of transitional care include coaching patients and caregivers on managing comorbid conditions that complicate the management of heart failure, developing effective communication with their physicians and fostering collaboration among care providers (including home care services) to deliver individualized care to patients and their caregivers (31,(33)(34)(35)(36)(37). Patient care is optimized when all health care professionals involved in the management of each patient agree on the care plan.…”
Section: Practical Tipsmentioning
confidence: 99%